Distopia nos games: narrativas digitais e o pensamento crítico - Salomão, Isabela Rodrigues (2023)
This project aims to discuss the role of narrative videogames in the construction of the current dystopic imaginary, as well as its potential as a tool in the development of critical thinking. To do so, three dystopic narrative games were selected: BioShock, Fallout and The Last of Us. First, the project briefly presents the situation of the discussion of games as a field of study. After that, it analyses the selected games. It relates the dystopia in BioShock with Ayn Rand’s objectivism and its association with neoliberal principals. Then, it presents the dystopia in Fallout, and proposes a correlation with Mark Fisher’s concept of capitalist realism. Finally, the project analyses the dystopia in The Last of Us, presenting its parallels with the current context. The research results make evident the need for expanding the efforts around the discussion of videogames as objects with potential for criticism